Modulation of Endothelial Bone Morphogenetic Protein Receptor Type 2 Activity by Vascular Endothelial Growth Factor Receptor 3 in Pulmonary Arterial Hypertension. Issue 23 (6th June 2017) - Hwangbo, Cheol; Lee, Heon-Woo; Kang, Hyeseon; Ju, Hyekyung; Wiley, David S.; Papangeli, Irinna; Han, Jinah; Kim, Jun-Dae; Dunworth, William P.; Hu, Xiaoyue; Lee, Seyoung; El-Hely, Omar; et al.
Abstract : Background: Bone morphogenetic protein (BMP) signaling has multiple roles in the development and function of the blood vessels. In humans, mutations in BMP receptor type 2 (BMPR2), a key component of BMP signaling, have been identified in the majority of patients with familial pulmonary arterial hypertension (PAH). However, only a small subset of individuals with BMPR2 mutation develops PAH, suggesting that additional modifiers of BMPR2 function play an important role in the onset and progression of PAH. Methods: We used a combination of studies in zebrafish embryos and genetically engineered mice lacking endothelial expression of Vegfr3 to determine the interaction between vascular endothelial growth factor receptor 3 (VEGFR3) and BMPR2. Additional in vitro studies were performed by using human endothelial cells, including primary lung endothelial cells from subjects with PAH. Results: Attenuation of Vegfr3 in zebrafish embryos abrogated Bmp2b-induced ectopic angiogenesis. Endothelial cells with disrupted VEGFR3 expression failed to respond to exogenous BMP stimulation. Mechanistically, VEGFR3 is physically associated with BMPR2 and facilitates ligand-induced endocytosis of BMPR2 to promote phosphorylation of SMADs and transcription of ID genes. Conditional, endothelial-specific deletion of Vegfr3 in mice resulted in impaired BMP signaling responses, and significantly worsened hypoxia-induced pulmonary hypertension. Consistent with these data, we found significant decrease in VEGFR3 expression in pulmonary arterial endothelial cells from human PAH subjects, and reconstitution of VEGFR3 expression in PAH pulmonary arterial endothelial cells restored BMP signaling responses. Conclusions: Our findings identify VEGFR3 as a key regulator of endothelial BMPR2 signaling and a potential determinant of PAH penetrance in humans. Abstract : Supplemental Digital Content is available in the text.